Penyuluhan Kesehatan Tentang Kesehatan Reproduksi Pada Siswa Kelas Xii Di Sma Negeri 12 Muara Bungo - Erni Yuniati (LPPM AN Nuur, 2021)
Background: Several studies show that the level of adolescent knowledge about reproductive health is still low. As research from (Rizky, 2010) states that of 73 students, 72.2% of them have less knowledge about adolescent reproductive health. The level of adolescent knowledge about reproductive health affects adolescent behavior in maintaining their reproductive health. If reproductive health education has been given to adolescents from an early age and started from the family, sex can be prevented. Lack of knowledge, nature and risky behavior in adolescents that have an impact on reproductive health status, adolescents need the availability of adolescent care health services that can meet the health needs of adolescents, especially services for adolescent-friendly reproductive health. Currently, several methods of health education regarding adolescent reproductive health have been developed, such as lectures and discussions, focus group discussions and health education. Purpose: To increase knowledge about reproductive health in class XII students at SMA N 12 Muara Bungo, Method: The method of applying science and technology is to provide counseling about reproductive health at SMA N 12 Muara Bungo which is carried out classically, lectures and questions and answers, all students class XII at SMA N 12 Muara Bungo who was present could take part in counseling activities on reproductive health. Results : From the results of the evaluation of the activities that have been carried out, the results obtained are in accordance with the objectives of the activity, namely 80% of participants can know what reproductive health is. Conclusion: From the activities that have been carried out, it can be concluded that there is an increase in the knowledge of class XII students at SMA N 12 Muara Bungo about reproductive health